Peran Guru Dalam Menangani Perilaku Mengganggu (Disruptive Behavior) Siswa Pada Proses Pembelajaran di Kelas [The Role of Teachers in Handling Disruptive Behavior Students in The Classroom Learning Process] - Serliana Christian; Dylmoon Hidayat (Diligentia: Journal of Theology and Christian Education, 2020)
Learning is an activity that involves interaction between teachers and students as achieving a learning goal. In the learning process, the teacher is required to carry out his role with full responsibility. If there is behavior in a class that does not support the learning process, the teacher must be able to take action correctly. Class management is needed by the teacher to create effective learning, and prevent problems in the classroom. Disruptive behavior that students do in the learning process must get treatment from the teacher because it will have an impact on other students. However, in addressing this problem the teacher must continue to see that students are the image of God, even if their behavior is not by God's truth. The teacher's role is to bring students to changes in behavior, as well as making students aware of their misbehavior. Therefore, this literature study aims to find out how the teacher's role in handling disruptive behavior of students in the learning process in class. The problem-solving approach used in the literature study method. Thus, the teacher can take a personal approach in good classroom management as his role in handling disruptive student behavior in class